Development of the model to predict the growth of Salmonella spp. in stirred fried rice with crab meat - Songamnat Pongsomboon (2018)
Central Composite Design (CCD) was used to study the main factors (temperature, pH, salt concentrations, initial inoculums and incubation time) affecting Salmonella enteritidis growth in stirred fried rice with crab meat. The result obtained from the CCD, fits in the second-order model using a quadratic polynomial equation. Y = 37.024 - 0.005 INOC + 7.7 × 10-7INOC2+ 0.001 INOC. pH + 3.5×10-4INOC.Time + 3.131 NaCl + 7.713 NaCl2- 6.8×10-5NaCl.INOC - 2.20 NaCLpH + 0.148 NaCl.Time -11.0 pH + 0.0927 pH2+ 0.037 pH.Time + 0.489 Temp - 0.003 Temp2- 2.3×10-4Temp.INOC - 0.056 Temp.NaCl - 0.019 Temp.pH + 0.007 Time.Temp - 0.619 Time - 6.00×10-4Time2. The model is developed for wider application. The new equation is as follows: Y = 37.024 - 0.005 INOC + 0.001 INOC. pH + 3.5×10-4INOC.Time + 3.131 NaCl + 7.713 NaCl2- 2.20 NaCl.pH + 0.148 NaCl.Time -11.0 pH + 0.0927pH2+ 0.037 pH.Time + 0.489 Temp - 0.003 Temp2- 2.3×10-4Temp.INOC - 0.056 Temp.NaCl - 0.019 Temp.pH + 0.007 Time.Temp - 0.619 Time. This new model is used to predict the population of Salmonella enteritidis, Salmonella amsterdam, Salmonella bangkok and Salmonella dublin in stirred fried rice with crab meat grew at different conditions. It is found that the new model accuracy is 94.93, 79.36, 88.39 and 96.33 per cent to predict growths of of Salmonella enteritidis, Salmonella amsterdam, Salmonella bangkok and Salmonella Dublin, respectively.